Diagnostic errors and treatment of anemia caused by vitamin B12 deficiency - V. V. Cherepanova; G. V. Sidnev; T. M. Konyshkina; V. I. Borisov; N. B. Moiseenko (Онкогематология)
This work was carried out in real clinical practice. Five clinical observations of anemia caused by vitamin B12 deficiency are presented, which demonstrate the difficulties of differential diagnosis. Differential diagnosis of B12‑deficiency anemia is carried out with folate deficiency anemia, hemolytic anemia, myelodysplastic syndrome, acute leukemia – erythromyelosis, aplastic anemia, myelocarcinomatosis, anemia due to copper deficiency. The relevance of the clinical problem is determined by the fact that B12‑deficiency anemia is one of the common anemias, the frequency of its detection varies in different age groups: after 60 years, vitamin B12 deficiency is found in one in 50 people, after 70 years – in every 15th. Currently, an increasingly common cause of megaloblastic anemia is vitamin B12 deficiency, which occurs while taking certain medications. Vitamin deficiency leads to a wide range of various disorders, primarily the occurrence of neurological manifestations, while there is insufficient awareness of clinicians about causes of its occurrence, nonspecific manifestations, diagnostic methods and effective therapy.